2015
DOI: 10.1021/ja512820k
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale Recognition of Surface Structure and Intercalation Mechanism of Ti3C2X

Abstract: MXenes represent a large family of functionalized two-dimensional (2D) transition-metal carbides and carbonitrides. However, most of the understanding on their unique structures and applications stops at the theoretical suggestion and lack of experimental support. Herein, the surface structure and intercalation chemistry of Ti3C2X are clarified at the atomic scale by aberration-corrected scanning transmission electron microscope (STEM) and density functional theory (DFT) calculations. The STEM studies show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
411
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(440 citation statements)
references
References 45 publications
28
411
0
1
Order By: Relevance
“…However, surface functional groups (O or F) and Ti are not supposed to be electrochemically active in aprotic ionic liquids. Intercalation of cations between MXene layers from aqueous electrolytes was observed by insitu XRD [6], and similar intercalation behavior was reported for MXene battery electrodes [18,19]. It is reasonable to assume that intercalation may occur in ionic liquid electrolytes as well.…”
Section: Introductionsupporting
confidence: 76%
“…However, surface functional groups (O or F) and Ti are not supposed to be electrochemically active in aprotic ionic liquids. Intercalation of cations between MXene layers from aqueous electrolytes was observed by insitu XRD [6], and similar intercalation behavior was reported for MXene battery electrodes [18,19]. It is reasonable to assume that intercalation may occur in ionic liquid electrolytes as well.…”
Section: Introductionsupporting
confidence: 76%
“…The mechanism of sodium intercalation into Ti 3 C 2 T x electrode was investigated using aberration-corrected scanning transmission electron microscopy [153] and solid-state 23 Na magic angle spinning NMR spectroscopy [154]. The atomic scale study by STEM showed that double layer of Na + ions can accommodate within the Ti 3 C 2 T x interlayer space upon deep discharge down to 0.0 V vs. Na/Na + ( Figure 14(e) and (f)).…”
Section: Transition Metal Carbides and Carbonitridesmentioning
confidence: 99%
“…Ti 3 C 2 T x electrode exhibited a reversible capacity of ≈200 mAh g −1 in Na-ion cells for 200 cycles. This high performance was attributed to the increased number of intercalation sites and large interlayer spacing of 9.8 Å which allow for the double-layer intercalation mechanism [153]. Solid-state NMR and XRD analyses demonstrated that the interlayer distance expands in the first sodiation process by 2.8 Å [154].…”
Section: Transition Metal Carbides and Carbonitridesmentioning
confidence: 99%
“…The unit cell of MXene Ti 3 C 2 has lattice constants a and b = 3.05Å, while the lattice constant c often describes the height of two adjacent sheets, see Figure 3.1d-f. The lattice constant c is 19.86Å for ideal Ti 3 C 2 MXene [122], while surface groups and intercalants expand the separation between sheets and increase the lattice constant between 0.18-9.8Å [114,127]. Apart from changing the separation between sheets, these surface groups and intercalants also influence the properties of MXene.…”
Section: Properties 21mentioning
confidence: 99%